Membangun Merek melalui Strategi Komunikasi Pemasaran (Proceeding Fakultas Ekonomi, 2011)
Marketing communications is an important thing that must be considered by marketers. The purpose of marketing communications of which this is to inform, persuade, and influence consumers to buy or use products that are offered. To communicate effectively, marketers need to understand the nine elements of the underlying fundamentals of effective communication that involves: (1) sender, (2) encoding, (3) message, (4) media, (5) decoding, (6) receiver, (7) response, (8) feed back, and (9) noise (Kotler and Keller, 2009: 514-515). Kotler and Keller (2009: 512) says there are eight kinds of marketing communications mix: advertising, sales promotion, events and experiences, public relations and publicity, direct marketing, interactive marketing, word-of-mouth marketing, as well as private sales.Brand is a major issue in product strategy. Under conditions of increasingly fierce competition, the brand plays a very important. For marketers, the brand is important to differentiate themselves from competitors. If a product or service that has a brand, product or service then it would be easy to distinguish from competitors. Marketers need to consider how appropriate communication strategy to build its brand in the eyes of consumers. Companies must realize that the market power it will be owned by companies with brand building. The brands that have been developed well will dominate the market and it will always be remembered by consumers. Brand is also a communication tool between the company and its customers. Through consumer brand then reveals his consciousness, identity, and choice. Brand later appeared as objects of consumer culture and ideology. Entanglement is not always the consumer with the brand again in a managerial perspective (economic) alone but also involves emotional aspects. It should be noted that marketers is how to communicate this brand to a company's reputation or image can be constructed with a strong brand.Keywords: marketing communications, promotion, message, advertising, brand